Assuming the square base is included as part of the surface area, the total surface area is

(total area) = (base area) + 4*(triangular face area)

189 cm^2 = 49 cm^2 + 4*(triangular face area) (put the given numbers into the equation)

140 cm^2 = 4*(triangular face area) (subtract the base area)

140/4 cm^2 = (triangular face area) (divide by 4)

(total area) = (base area) + 4*(triangular face area)

189 cm^2 = 49 cm^2 + 4*(triangular face area) (put the given numbers into the equation)

140 cm^2 = 4*(triangular face area) (subtract the base area)

140/4 cm^2 = (triangular face area) (divide by 4)

**35 cm^2 = (triangular face area)**